Highly enhanced field emission properties of a carbon nanotube cathode on a titanium alloy substrate modified by alkali. (August 2021) - He, Siru; Hong, Xuda; Zheng, Hairong; Liang, Dong
Abstract: Field emission electron sources with low turn-on electric fields, high emission current density, and good stability are of paramount importance in widespread applications, and in particular vacuum nanoelectronic equipment. Herein, an alkali modification approach was rationally designed to tailor the morphology of the commonly used compact and planar titanium alloy substrate. As expected, the modified substrate exhibited an interconnected porous network morphology, which offers remarkably strengthened adhesion with the screen-printed carbon nanotube cathode atop. As a result, the devices delivered comprehensively improved performance. Specifically, in the continuous driving mode, the turn-on electric field was as low as 0.79 V/μm, while the emission current of 85.13 mA/cm 2 was relatively high. In parallel, in the pulse driving mode, the emission current density reached 1.266 A/cm 2 under an electric field of 6.1 V/μm. Encouragingly, the cathode exhibited rather decent emission stability even under continuous operation for hours. This work provides a practical strategy for further enhancement of the field emission performance of carbon nanotube cathodes and highlights the significance of engineering titanium alloy substrates in future development. Highlights: AAlkali modification is crucial for rationally designed the morphology of the titanium alloy substrate. The optimal growth time of porous network morphology were investigated. The investigation shows the strengthened adhesion between substrate and carbon nanotube atop. With the addition of titanium powder, the emission current density reaches 1.266 A/cm 2 under an electric field of 6.1 V/μm.